How (and How Not) to Defend Lesser-Evil Options - Gordon-Solmon, Kerah (Journal of moral philosophy, 2023)
Many philosophers believe in lesser-evil justifications for doing harm: if the only way to stop a trolley from killing five is to divert it away onto one, then we may divert. But recently, Helen Frowe has argued that we do not only have the option to pursue the lesser evil: in most cases, we are so obligated. After critically assessing Frowe’s argument, I develop three mutually compatible accounts of lesser-evil options, which permit, but do not obligate us to minimize harm. These are the Parity Account, the Prerogative Account, and the Permissible Moral Mistakes Account. Considerations of parity and prerogatives have arisen in this debate before, but in inchoate form. The Permissible Moral Mistakes Account introduces something new.